The Effect of Functional Classification of Wheelchair Basketball Players on Blood Pressure Values after Physical Activity - Alkhawaldeh, Ibtehal; Tabazah, Mohnnad (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to identify the impact of the functional classification of wheelchair basketball players on blood pressure values after sub-maximal exercise. Methods: the researchers used semi-experimental method with all its procedures to achieve the study objectives. The study sample consisted of (8) players out of the (12) players representing the Jordan national wheelchair basketball team based on the records of the Jordan Paralympic Committee for years 2021, and the players were selected deliberately. The researchers used the semi-experimental method to achieve the study objectives. Moreover, the researchers used the VO2PEAK test and Borg scale of perceived severity statistically, the One Way ANOVA test and the LSD test were used, in addition to the arithmetic mean. Results: The results showed a significant decrease in the value of diastolic blood pressure in the categories (1-1.5) and (2-2.5). This took place lower due to the nature of the disabilities falling under these two categories are according to the classification of wheelchair basketball players. Conclusions: In light of the results, the researchers recommend taking into consideration the values of diastolic blood pressure when developing training programs, especially for players with amputations from the classification of amputations of the lower limbs above the knee.